Review of the components in business models of sustainable tourism companies - Mendoza-Ramírez, Edith; Garnica-González, Jaime; Cruz-Coria, Erika (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research, the business models of sustainable tourism companies reported in the last 11 years are studied, in order to identify the main components attached to compliance with the principles of sustainability in tourism. For this, the content analysis methodology was used, obtaining the identification of components with recurrences from higher to lower appearance in the business models of sustainable tourism companies, in order to generate areas of opportunity in the creation of systemic models oriented to this type of companies.